Mine tailings-based geopolymers: A comprehensive review. Issue 17 (1st September 2022) - He, Xiang; Yuhua, Zuhua; Qaidi, Shaker; Isleem, Haytham F.; Zaid, Osama; Althoey, Fadi; Ahmad, Jawad
Abstract: The mining industry produces a large amount of stone waste and tailings, which poses a threat to the environment. Dumping is the most common means of disposing of this industrial waste, contributing to soil degradation and water pollution with the acquisition of valuable land. Fortunately, it can be recycled in a variety of technologies, including the promising geopolymerization technology, which turns waste into value. This review paper presents recent advances in the production of mine tailings-based geopolymer composites from industrial waste as a potential sustainable building material. This article also provides in-depth studies on the behaviors and characteristics of mine tailings composites utilized in geopolymer production, such as physical properties, mechanical properties, durability properties, microstructural properties, thermal properties, leaching behavior, and potential applications. Besides, study developments are moving towards a comprehensive understanding of the environmental footprints and economic benefits of mine tailings-based geopolymer composites for building applications utilizing mine tailings as suitable concrete material. This review paper also highlights knowledge gaps that must be overcome to progress mine tailings composites for geopolymers, as well as future study opportunities based on prior research and existing challenges.